P2X7 receptor isoform B is a key drug resistance mediator for neuroblastoma - Arnaud-Sampaio, Vanessa Fernandes; Bento, Carolina Adriane; Glaser, Talita; Adinolfi, Elena; Ulrich, Henning; Lameu, Claudiana (Frontiers in Oncology, 2022)
Drug resistance is a major challenge for all oncological treatments that involve the use of cytotoxic agents. Recent therapeutic alternatives cannot circumvent the ability of cancer cells to adapt or alter the natural selection of resistant cells, so the problem persists. In neuroblastoma, recurrence can occur in 50% of high-risk patients. Therefore, the identification of novel therapeutic targets capable of modulating survival or death following classical antitumor interventions is crucial to address this problem. In this study, we investigated the role of the P2X7 receptor in chemoresistance. Here, we elucidated the contributions of P2X7 receptor A and B isoforms to neuroblastoma chemoresistance, demonstrating that the B isoform favors resistance through a combination of mechanisms involving drug efflux via MRP-type transporters, resistance to retinoids, retaining cells in a stem-like phenotype, suppression of autophagy, and EMT induction, while the A isoform has opposite and complementary roles.